Impact of genotypes, environmental stresses, and genotype by environment interactions on growth and yield of quinoa at flowering stage - Van Loc Nguyen; Trung Hieu Do; Thi Hong Nhung Phan; Viet Long Nguyen; Duc Ha Chu; Daniel Bertero; Néstor Curti; Viet Ton Ta; Peter C. McKeown; Charles Spillane (PLoS ONE, 2025)
Flowering is a critical growth stage of quinoa (Chenopodium quinoa Willd.), with a strong influence on growth and grain yield. To understand factors affecting such flowering stage effects, we measure the differential effects of genotype (G), environmental stress (E), and genotype by environment interaction (G × E) on quinoa growth and yield-related traits during the flowering stage. A semi-controlled pot experiment was conducted in a greenhouse using a Randomized Complete Block Design (RCBD) with five replications. Five quinoa genotypes (Q1, Cahuil, G18, Isluga, and Q3) were evaluated under four climate-related stress vs non-stress treatment conditions: control (E1), waterlogging (E2), salinity (E3), and drought (E4). Morphological and yield traits, including plant height, number of tillers and leaves, leaf area, soil plant analysis development (SPAD) values, fresh and dry biomass, panicle length, 1000-grain weight, and individual grain yield were measured. There were significant effects of G, E, and G × E interaction on all measured traits, indicating considerable variation in genotype adaptability to abiotic stresses. The order of stress severity was E2 > E4 > E3 > E1, with waterlogging causing the most substantial reductions across growth and yield traits. The AMMI analysis highlighted strong genotype-specific responses across environments. Our findings provide insights into how quinoa responds to environmental stresses, supporting the development of research strategies and and irrigation management for quinoa under climate change related stresses.